2021
DOI: 10.1002/ijgo.13946
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of vaginal birth after cesarean for labor dystocia by sonographic estimated fetal weight

Abstract: Elective repeat cesarean delivery (ERCD) carries an inherent risk for maternal morbidity and economic costs. Therefore, reducing the rising rates of ERCD worldwide is paramount. 1,2 Trial of labor after cesarean (TOLAC) is an alternative to ERCD and represents an effective option to reduce cesarean delivery rates. When successful vaginal birth after cesarean (VBAC) is achieved, it is associated with lower rates of perinatal adverse outcomes. 1,3 As failure of TOLAC is associated with adverse neonatal and mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Multiple logistic regression analysis showed that induction of labor was positively associated with TOLAC failure. Cohort studies conducted in India and Israel also showed that labor induction was independently associated with failed TOLAC [9,15,23]. The rate of IOL was also higher (16.7%) in the VBAC group in Caroline' study [18].…”
Section: Discussionmentioning
confidence: 87%
“…Multiple logistic regression analysis showed that induction of labor was positively associated with TOLAC failure. Cohort studies conducted in India and Israel also showed that labor induction was independently associated with failed TOLAC [9,15,23]. The rate of IOL was also higher (16.7%) in the VBAC group in Caroline' study [18].…”
Section: Discussionmentioning
confidence: 87%
“…A large number of predictive models of trial of labor after cesarean delivery have been reported in China and abroad 11,13,15,22,25–28 . However, most studies were based on maternal obstetric characteristics, and some only combined fetal birth weight or estimated fetal weight near term.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of predictive models of trial of labor after cesarean delivery have been reported in China and abroad. 11,13,15,22,[25][26][27][28] However, most studies were based on maternal obstetric character- fetal head circumference obtained from ultrasound. Some scholars have established a prediction model for the success rate of VBAC, including several more typical models, such as the Grobman nomogram, 11 Smith, 21 and Gonen 29 models.…”
Section: Discussionmentioning
confidence: 99%